Enhancing Grammatical Skills through Recounting the YouTube Video to Improve Speaking Ability - Edy Suseno; Oikurema Purwati; Syafiul Anam (Pusat Studi Bahasa dan Publikasi Ilmiah, 2023)
Delivering ideas to others involves speaking in a significant way. Information exchange amongst language users is facilitated by this. However, many EFL students had difficulties when they tried to practice speaking. During the delivery, they stutter and become stuck. Ten freshmen attend the therapy to address these faults. It modifies YouTube content to enhance students' speaking abilities. To understand how to create sentences, the session began by using lexicogrammar. The instructor requested that the student study and retell a grammar video from YouTube in order to improve understanding. The students watched a vocabulary film on YouTube and then learnt and repeated the topic to increase their vocabulary. They then studied and repeated the information from a YouTube video that described the image. The teacher invited the students to describe photos using both written and spoken language in order to observe the students' growth in their vocabulary, grammar, and speaking abilities. The instructor provided feedback in the most recent class. The information gathered during the procedure was qualitatively examined. The study's findings led to an improvement in the students' speaking abilities by helping them with their grammar, vocabulary, and pronunciation. This kind of discovery could be used by teachers to teach the pertinent subjects. Additionally, it motivates additional researchers to study relevant topics.